The ethics of our climate hermeneutics and ethical theory - O'Neill, William R. (Georgetown Univ. Press, 1994)
In this book, William O'Neill, S.J., offers an interpretation of the nature and scope of practical reasoning in light of postmodern philosophical criticism. He charts a via media between the abstract formalism of neo-Kantian morality and relativist interpretations of neo-Aristotelian ethics. The three parts of the book treat the eclipse of the classical Aristotelian conception of practical reason; the Kantian heritage in the modern moral theories of John Rawls and R.M. Hare; and the hermeneutical retrieval of a moral interpretation of the world. Drawing upon the philosophical hermeneutics of Hans-Georg Gadamer, modern analytical philosophy, and the discourse ethics of Jurgen Habermas, O'Neill offers a critical reconstruction of practical reason which upholds the primacy of moral community while recognizing the ethical import of historical and cultural difference. The final chapter applies the preceding hermeneutical critique to the question of the distinctiveness of Christian ethics in the writings of Karl Barth, Hans Urs von Balthasar, Josef Fuchs, and Bruno Schuller. This original contribution will be of special interest to students and teachers of moral philosophy and theology.
Keywords: Geschichte 1900-2000; Ethics; Ethics, Modern -- 20th century; Hermeneutics; Postmodernism; Hermeneutik; Ethik; Postmoderne